บุคลิกภาพกับการมีส่วนร่วมทางการเมืองของครูประชาบาล จังหวัดอุบลราชธานี - ประยงค์ บัตรสมบูรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1980)
This study examines certain types of personality of teachers in Ubon ratchathani province. The main purpose is to delineate the teachers’ personalities in order to describe the personality that is conducive or obstructive to the development of democratic form of government. It is also to illuminate relationships of personalities and degree of political participation. This thesis is a result of a survey research six hundred teachers from eight amphur were chosen for the study. 208 teachers who were working in three amphur designated as sensitive area could answer questionaires completely, so did the 282 teachers in non-sensitive area covering five amphur. A questionnaire consists of 34 items. Each item was tested by discriminative power, content validity and reliability. The three variables which the researcher look into were democratic and [authoritarian] personality and political participation, were taken as dependent variables while operational areas, level of education, sex and ages were treated as independent variables. The findings of this study may be summed up as follow : 1. Political Personality of the majority of the teachers are both democratic and authoritarian. The level of participation of both types of teachers is high. 2. Difference in age and operational area are not a major determinant of the teachers’ personality and political participation. 3. The majority of male teachers have democratic personality, while the majority of female teachers have authoritarian personality; moreover, male teachers have higher degree of political participation than female teachers. 4. Higher educated teachers exhibit democratic personality; while lower educated teachers trend to have authoritarian personality; moreover, higher educated teachers have higher degree of political participation than lower educated teachers. In conclusion, the majority of teacher in Ubon ratchathani have both types of personality which is the normal form of people in the developing country. If the majority of teachers in Thailand had, it would not be conducive to the development of democratic government.